2011
DOI: 10.2147/vaat.s17832
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hypoxia on oncolytic virotherapy

Abstract: Abstract:The hypoxic tumor microenvironment plays significant roles in tumor cell metabolism and survival, tumor growth, and progression. Hypoxia modulates target genes in target cells mainly through an oxygen-sensing signaling pathway mediated by hypoxia-inducible factor of transcription factors. As a result, hypoxic tumor cells are resistant to conventional therapeutics such as radiation and chemotherapy. Oncolytic virotherapy may be a promising novel therapeutic for hypoxic cancer. Some oncolytic viruses ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…For example, oncolytic adenovirus replication is hampered under hypoxic conditions, while oncolytic HSV-1 replication is enhanced under hypoxic conditions. Oncolytic Vaccinia virus demonstrates improved cytotoxicity in hypoxic cancer cells, but has no increase in transgene expression [144]. Some studies have also demonstrated that inhibition of the mTOR pathway can also be detrimental for immunotherapy.…”
Section: Considerations For Targeting Hypoxia-induced Pathwaysmentioning
confidence: 99%
“…For example, oncolytic adenovirus replication is hampered under hypoxic conditions, while oncolytic HSV-1 replication is enhanced under hypoxic conditions. Oncolytic Vaccinia virus demonstrates improved cytotoxicity in hypoxic cancer cells, but has no increase in transgene expression [144]. Some studies have also demonstrated that inhibition of the mTOR pathway can also be detrimental for immunotherapy.…”
Section: Considerations For Targeting Hypoxia-induced Pathwaysmentioning
confidence: 99%
“…Recently, oncolytic virotherapy has garnered interest as potential therapeutic strategy for hypoxic tumors [29] . A hypoxia-responsive promoter that is upregulated by HIF-1 has been used for the tumor-specific replication of an oncolytic adenovirus [30] [32] .…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of OVs in cancer therapy poses several challenges, including the issues of Limited Virus Penetration, patient selection, passive targeting, immune responses and hypoxia (100)(101)(102). In order to overcome these challenges that OV monotherapy is facing, today the attention of scientists in this field has been drawn to the genetic engineering of these viruses in order to express cytokines, chemokines, and also recombinant antibodies.…”
Section: Overview Of the Oncolytic Viruses And Cancer Immunotherapymentioning
confidence: 99%